Cost effectiveness analysis of typhoid fever vaccination in an endemic district of Kabale, Uganda - Odulusi, Daniel (International Journal Of Community Medicine And Public Health, 2022)
Background: Typhoid fever is a preventable disease that affects the livelihood security of households and communities, accounting for a significant portion of the disease burden in Kabale district. Various preventive programs to control this burden such as curative services and vaccination are being implemented without empirical evidence of the effectiveness of either program in terms of costs and outcomes. Methodology: The study design is a mixed methods design in which for specific research objectives a cross-sectional survey was carried out in addition to a retrospective costing analysis. The outcome being a cost effectiveness evaluation of vaccination against typhoid with the comparator being no vaccination, expressed as the incremental cost effectiveness ratio. Results: Incidence rate of 39.8 per 1000, a case fatality rate of 0.061, and cost of illness of $75.62 for inpatient care and $33.85 for an outpatient case, with an average cost of illness of typhoid fever in Kabale district to be $54.74. In addition, typhoid fever costs Kabale district $217,158.8, of which $119,814.92 could be saved if a typhoid fever vaccination program is carried out, that will avert 2,189 cases of typhoid every year for three years. Vaccination results in 28,428.32 DALYs avoided. The resulting ICER of -6.348 reveals that the vaccination program against typhoid fever is both extremely cheaper and very effective in averting both typhoid cases and costs. Conclusions: a one-time fixed-post typhoid vaccination campaign in Kabale District, Uganda, was estimated to be a very highly cost-effective intervention from the public sector health care delivery perspective.